Predicting Choice Behavior of Group Members - Spieß, Lukas; Bekkering, Harold (Frontiers in Psychology, 2020)
Meaningful social interactions rest upon our ability to accurately infer and predict other people’s preferences. In doing so, we can separate two sources of information: knowledge we have about the particular individual (individual knowledge) and knowledge we have about the social group to which that individual belongs (categorical knowledge). However, it is yet unclear how these two types of knowledge contribute to making predictions about other people’s choice behavior. To fill this gap, we had participants learn probabilistic preferences by predicting object choices of agents that either belonged to a social group (Group condition) or not (Individual condition). We quantified how close predictions for a specific agent are relative to the objective individual preferences of that agent and how close these predictions are relative to the objective group-level preferences to which that agent belongs. As expected, we found that participants’ predictions in the Group condition, relative to the Individual condition, were more similar to the group-level preference, while less similar to the individual-level preferences. We interpret this pattern of results as indicative of a differential weighting of individual and categorical group knowledge when making predictions about individuals that belong to a social group. The results are interpreted in an assimilation account of categorization and stress the importance of group knowledge during daily social interactions.